2024
DOI: 10.3390/rs16040669
|View full text |Cite
|
Sign up to set email alerts
|

A Space Target Detection Method Based on Spatial–Temporal Local Registration in Complicated Backgrounds

Yueqi Su,
Xin Chen,
Chen Cang
et al.

Abstract: Human space exploration has brought a growing crowded operating environment for in-orbit spacecraft. Monitoring the space environment and detecting space targets with photoelectric equipment has extensive and realistic significance in space safety. In this study, a local spatial–temporal registration (LSTR) method is proposed to detect moving small targets in space. Firstly, we applied the local region registration to estimate the neighbor background motion model. Secondly, we analyzed the temporal local grays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The authors also explored different technologies for data analysis, including machine learning, genetic algorithms, and recurrent neural networks. They concluded that weather conditions, illumination variability, and dynamic background scenes could affect the results of the detection algorithm [12].…”
Section: Related Workmentioning
confidence: 99%
“…The authors also explored different technologies for data analysis, including machine learning, genetic algorithms, and recurrent neural networks. They concluded that weather conditions, illumination variability, and dynamic background scenes could affect the results of the detection algorithm [12].…”
Section: Related Workmentioning
confidence: 99%